Potential spread of mcr-9-carrying IncHI2 plasmids in Enterobacter hormaechei in Vietnam - Van Thi Thu Ha (Elsevier, 2021)
ABSTRACT: Objectives: Mobile colistin resistance (mcr) genes are widely distributed around the world. To date, ten major variants of mcr genes are known (mcr-1 to mcr-10). However, only a few instances of Enterobacterales isolates harbouring mcr genes other than mcr-1 have been reported in Vietnam. The aim of this study was to investigate mcr-harbouring antimicrobial-resistant Enterobacterales isolates in Vietnam. Methods: Two mcr-9-harbouring Enterobacter hormaechei clinical isolates (NIHE14-1904 and MH17-539M) were obtained from medical institutions in Hanoi, Vietnam, in 2014 and 2017, respectively. Their genomes and plasmid sequences were analysed by short-read and long-read sequencing. Subsequently, comparative sequence analysis of their mcr-9-carrying plasmids was performed. Results: Strains NIHE14-1904 and MH17-539M belonged to sequence types ST916 and ST66, respectively, according to the Enterobacter cloacae multilocus sequence typing (MLST) scheme. NIHE14-1904 and MH17-539M harboured the mcr-9 gene on similar IncHI2 plasmids, namely pNIHE14-1904-mcr9 (373.1 kb) and pMH17-539M-mcr9 (289.3 kb), respectively. These plasmids were also highly identical to widespread IncHI2 plasmids that are often associated with mcr genes. Conclusion: For the first time, mcr-9-harbouring Enterobacterales isolates were detected in Vietnam, which carried mcr-9 on IncHI2 plasmids. The prevalence of such plasmids needs to be monitored in the future owing to their high dissemination.